Antioxidant Responses Induced by UVB Radiation in Deschampsia antarctica Desv. - Köhler, Hans; Contreras, Rodrigo A.; Pizarro, Marisol; Cortés-Antíquera, Rodrigo; Zúñiga, Gustavo E. (Frontiers in Plant Science, 2017)
Deschampsia antarctica Desv. is one of two vascular plants that live in the Maritime Antarctic Territory and is exposed to high levels of UVB. In this work, antioxidant physiology of D. antarctica was studied in response to UVB induced oxidative changes. Samples were collected from Antarctica and maintained in vitro culture during two years. Plants were sub-cultured in a hydroponic system and exposed to 21.4 kJ m-2 day-1, emulating summer Antarctic conditions. Results showed rapid and significant increases in ROS at three hours, which rapidly decreased. No dramatic changes were observed in photosynthetic efficiency, chlorophyll content and level of thiobarbituric acid reactive species (MDA). The enzymatic (superoxide dismutase, SOD and total peroxidases, POD) and non-enzymatic antioxidant activity (total phenolic) increased significantly in response to UVB treatment. These findings suggest that tolerance of D. antarctica to UVB could be attributed to its ability to activate both enzymatic and non-enzymatic antioxidant systems.